ANALISIS STATISTIK ANGKA PERCERAIAN DI KABUPATEN BEKASI TAHUN 2025 MENGGUNAKAN METODE ARIMA - Darmawan, Dery; Saputra, Andri; Mirtawati, Mirtawati (Matematika Sains, 2025)
Divorce cases in Bekasi Regency have shown an increasing trend in recent years. Contributing factors include economic pressure, poor communication, and the influence of social media. This study aims to forecast the divorce rate in Bekasi Regency using the Autoregressive Integrated Moving Average (ARIMA) method. The data used are monthly divorce rates from January 2020 to May 2025. The analysis shows that the best model is ARIMA (1,0,6), selected based on the smallest AIC and SC values ​​and passing diagnostic tests (autocorrelation, normality, and stability). The forecasting accuracy rate is 22.96%, which can be categorized as quite good. Based on this model, the ARIMA (1,0,6) model is suitable for predicting divorce rates and can serve as an initial reference for policymakers.